Gender stereotypes and price dynamics in the sharing economy: Evidence from a car sharing platform - Marco Percoco; Peter Schmidt (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2019)
Gender stereotypes are increasingly considered to be as important as gender discrimination in market transactions. In this paper, we show that they influence market outcomes also through the client feedback channel of online platforms. Using a novel panel dataset of listings on the largest peer-to-peer car sharing platform in the U.S., we show that, controlling for quality of the listing, female renters leave more positive reviews. While positive reviews generally induce car owners to increase asking prices, the increase is significantly lower in the case the review was written by a female renter. This finding is consistent with platform users (both males and females) affected by gender stereotypes and implies that price dynamics in peer-to-peer market are affected by priors regarding reviewers ability to appreciate qualities of the good.
Keywords: D47; L11; L81; L86; 330; Gender stereotypes; peer-to-peer markets; sharing economy; car rental